Transcription factor 4 expression and correlation with tumor progression in gallbladder cancer - Neogi K.; Tewari M.; Singh A.K.; Sharma K.; Tej G.N.V.C.; Verma S.S.; Gupta S.C.; Nayak P.K. (My University, 2025)
Background: Dysregulation in Wnt/β-catenin signaling has been associated with the initiation and metastasis of cancer cells. Transcription factor 4 (TCF4) (also named as transcription factor 7-like 2) is a key transcriptional factor of the Wnt signaling pathway, which, when interact with β-catenin activates Wnt genes which plays an essential role in tumor development. The expression pattern and clinical significance of TCF4 in gallbladder cancer (GBC) are not yet established. Aims: This study was performed to assess the expression pattern of TCF4 in GBC tissue and attempted to correlate its expression with different clinicopathological parameters. Materials and Methods: The study was conducted on 33 surgically resected specimens of gallbladder carcinoma (GBC) and 12 cases of chronic cholecystitis (CC) as control, which had been confirmed from histology. The expression of TCF4 was performed by the reverse transcription polymerase chain reaction and immunohistochemistry. Results: Relative mRNA expression levels of β-catenin and TCF4 in GBC tissues were significantly (P < 0.05) higher than in CC samples. TCF4 protein expression was observed in 81.82% (27/33) GBC cases. Specifically, among GBC samples, 21.21% (7/33) was graded as strongly positive, 60.61% (20/33) graded as moderately positive, whereas 18.18% (6/33) graded as negative. All 12 CC samples graded as negative. Overall, TCF4 expression in GBC tissues was statistically significant over CC samples (P < 0.05). Moreover, we observed that TCF4 expression was significantly higher (P < 0.05) in high tumor grades than low grade, higher (P < 0.05) in Stage 2 and Stage 3 than Stage 1. Conclusion: The present study suggests that TCF4 may exert an oncogenic role in the progression of GBC and may serve as a new potential candidate biomarker for tumor progression, and it might be a potential therapeutic target against GBC. © 2022 Journal of Cancer Research and Therapeutics.